Magnetic field assisted surface laser shock strengthening hard alloy device and method

Through magnetic field-assisted surface laser impact strengthening technology, the gradient structure of cemented carbide is formed, which solves the problem of insufficient mechanical properties of existing cemented carbides and significantly improves hardness, strength and life.

CN119592894APending Publication Date: 2025-03-11NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411589912.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing cemented carbides are insufficient in modern cutting processing, making it difficult to meet the problems of high wear and low life.

Method used

Magnetic field-assisted surface laser impact strengthening technology is used to form high residual compressive stress on the surface of cemented carbide, migrate internal metal phases and distribute them evenly, forming a gradient structure to improve hardness and strength.

Benefits of technology

It significantly improves the mechanical properties of cemented carbides, including hardness, strength and relative density, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592894A_ABST
    Figure CN119592894A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic field assisted surface laser shock strengthening hard alloy device and method, the device comprises a laser galvanometer, a container and a magnetic field generator, a hard alloy sample to be processed is placed in the container, deionized water covers the hard alloy sample to be processed in the container, and the magnetic field generator comprises two Helmholtz coils; a uniform magnetic field is formed between the two Helmholtz coils, the container is arranged between the two Helmholtz coils, the laser galvanometer is aligned with a hard alloy sample to be processed, and the laser galvanometer can generate an infrared laser beam to perform laser shock peening on the hard alloy sample to be processed. According to the method, the alternating magnetic field is applied to the surface of the workpiece through the electromagnetic field, migration of the Co phase is accurately regulated and controlled, distribution of the ceramic phase and the metal phase is improved, and active regulation and control of the surface microstructure are achieved. And surface oxide layer refining grains are removed through alternating magnetic field assisted laser shock peening, a gradient structure is generated on the surface layer, and the mechanical property of the hard alloy is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface modification, and in particular relates to a magnetic field assisted surface laser shock strengthening device and method for cemented carbide. Background Art

[0002] Cemented carbide is a composite material composed of a hard phase and a metal phase in a certain ratio. It has the characteristics of high hardness of ceramics and high strength of high-speed steel. The ratio and distribution of WC particles and Co binder in cemented carbide will affect its wear resistance. The increase in Co content can improve the toughness and impact resistance of cemented carbide, but too much may lead to a decrease in wear resistance. The size and distribution of WC particles will also affect the wear performance. The finer the particles, the better the wear resistance. With the development of modern industry, more and more new materials are used in industries such as aerospace, automobiles, and molds. The difficulty of cutting processing continues to increase, resulting in serious wear of tools and molds and low life. Existing cemented carbides are not enough to meet the requirements of modern cutting processing.

[0003] Therefore, how to improve the mechanical properties has become an urgent need. Chinese patent document CN 118186202 A provides a strengthening method and device for ferromagnetic metals using static magnetic field coupling laser shock strengthening. The method applies a static magnetic field to the ferromagnetic metal for a period of time, coats the surface with black tape, and uses a laser to perform single-point strengthening on the surface. This method is suitable for strong magnetic materials and metal materials will not affect the propagation of shock waves in the material. However, the static magnetic field cannot adjust the response of the magnetic field and the magnetic material during the processing. The alternating magnetic field generated by the electromagnet can adjust the magnetic field intensity and magnetic field direction by adjusting the input current during the processing to achieve the adjustable distribution of magnetic materials. Cemented carbide is mainly composed of ceramic phase WC and weak magnetic material Co. The hard ceramic phase and surface oxides will affect the formation and propagation of shock waves in the material, and the presence of black tape will also affect the response of weak magnetic Co to the magnetic field. Therefore, the present invention first proposes a method of using low pulse energy and water as a constraining layer to reduce the damage to the material caused by excessive laser energy, increase the strengthening range, and assist the laser shock strengthening process through the response of the alternating magnetic field and the weak magnetic Co, and regulate the metal phase and microstructure changes during the laser shock strengthening process. It is of great significance to improve the mechanical properties, improve the wear during the processing of difficult-to-process materials, improve the surface integrity of the workpiece and extend the service life of cemented carbide materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a magnetic field assisted surface laser shock strengthening device and method for cemented carbide in view of the above-mentioned existing deficiencies. The surface of the cemented carbide material prepared by this method produces high residual compressive stress, the internal metal phase migrates to the surface under the action of pressure, and is evenly distributed on the surface of the material under the control of the magnetic field. The grains show a gradient distribution in the depth direction, and have high hardness, high strength, and good life.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0006] A magnetic field-assisted surface laser shock strengthening device for cemented carbide comprises a laser galvanometer, a container and a magnetic field generator. The cemented carbide sample to be processed is placed in the container, and the cemented carbide sample to be processed is covered with deionized water in the container. The magnetic field generator comprises two Helmholtz coils, and a uniform magnetic field is formed between the two Helmholtz coils. The container is placed between the two Helmholtz coils. The laser galvanometer is aligned with the cemented carbide sample to be processed. The laser galvanometer can generate an infrared laser beam to perform laser shock strengthening on the cemented carbide sample to be processed.

[0007] To optimize the above technical solutions, the specific measures taken also include:

[0008] The magnetic field generator is connected to a magnetic field generating device power supply via a magnetic field generating device power supply line, and the magnetic field generating device power supply can change the magnetic field intensity of the magnetic field generator by changing the input current.

[0009] The above-mentioned magnetic field-assisted surface laser shock strengthening cemented carbide device also includes a laser operation console, a laser galvanometer lifting structure and a sample table. The laser operation console includes a control device and a display screen. The laser galvanometer lifting structure includes a lifting motor and a lifting rod. The laser galvanometer is installed on the lifting rod, and the lifting rod is installed on the lifting motor. The control device is connected to the lifting motor signal. The control device can control the operation of the lifting motor to lift the lifting rod. The control device is connected to the display screen, and the display screen is used to display the control information of the control device. The sample table is located between two Helmholtz coils, and the container is placed on the sample table.

[0010] A magnetic field assisted surface laser shock strengthening method for cemented carbide, using the magnetic field assisted surface laser shock strengthening device for cemented carbide, specifically comprising the following steps:

[0011] S1, cutting the cemented carbide into block blanks by electric spark wire cutting;

[0012] S2. Roughly grind the block blank to remove the ablated surface produced by wire EDM to obtain a smooth surface;

[0013] S3, cleaning the block blank, removing the oil and impurities on the surface, and obtaining the cemented carbide sample to be processed;

[0014] S4, placing the hard alloy sample to be processed into a container, and covering the hard alloy sample to be processed with deionized water as a constraining layer;

[0015] S5, placing the container between the two Helmholtz coils, setting the input current, input voltage and frequency of the magnetic field generator so that each Helmholtz coil generates an alternating magnetic field, and the magnetic field between the two Helmholtz coils is a uniform magnetic field;

[0016] S6. Start the laser galvanometer, which performs laser shock peening on the surface of the hard alloy sample to be processed through an infrared laser beam, so as to obtain the hard alloy induced by laser shock peening.

[0017] In S2, the block blank is roughly ground using a surface grinder to remove the ablated surface produced by electric spark wire cutting. The ablated surface removal depth ranges from 10 to 50 μm, and the surface wear marks are removed using diamond grinding paste to obtain a flat surface. The surface roughness of the flat surface is Ra0.1-0.2.

[0018] In S3, the block blank is placed in a container containing alcohol, and the surface oil and impurities are removed by ultrasonic cleaning for 15 minutes to obtain the cemented carbide sample to be processed.

[0019] In S4, ionized water is used as a constraining layer to cover the cemented carbide sample to be processed, and the water surface of the constraining layer is 0.2-1.5 mm higher than the upper surface of the cemented carbide sample to be processed.

[0020] In S5, the input current of the magnetic field generator is 10-15A, the input voltage is 150-250V, the frequency is 40-50Hz, and the uniform magnetic field intensity generated by the two Helmholtz coils is within 0-60mT.

[0021] In S6, the power of the infrared laser beam generated by the laser galvanometer is 2-16W, the laser scanning path spacing range is 0.05mm-0.15mm, the laser spot overlap rate is 50%, and the scanning times of the laser shock strengthening hard alloy sample to be processed range from 1 to 5 times.

[0022] The wavelength of the infrared laser beam is 1064nm.

[0023] Compared with the prior art, the present invention has significant improvements:

[0024] The present invention overcomes the problem of insufficient strength and hardness of existing cemented carbide and develops a new magnetic field-assisted surface laser shock strengthening technology for improving the mechanical properties of cemented carbide. First, the cemented carbide sample to be processed is placed in a container, deionized water is added to cover the sample, then the magnetic field generating device is turned on, the magnetic field strength is set, and then the laser is turned on to set the laser scanning path, laser scanning frequency, laser power, and scanning times, and the upper and lower surfaces of the cemented carbide are laser-shock-strengthened in turn to obtain a cemented carbide with excellent mechanical properties.

[0025] The present invention realizes the surface strengthening technology of cemented carbide through a special process. On the one hand, the mechanical properties are significantly improved, and the mechanical properties of cemented carbide are improved. The processing method is simple and the production cost is low. On the other hand, this strengthening method does not need to add a reinforcing phase to change the phase composition of the material. The method changes the grain size through laser impact, reduces the porosity, and increases the relative density. The distribution of the internal metal phase is regulated by a magnetic field to form a gradient structure with small surface grains and large middle grains, which solves the shortcomings of homogeneous cemented carbide materials, such as high brittleness, low transverse fracture strength, and poor impact load bearing capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The SEM picture and grain size statistics of the cemented carbide material prepared by the present invention;

[0027] Figure 2 It is a schematic diagram of the structure of a magnetic field-assisted surface laser shock strengthening device for cemented carbide.

[0028] The accompanying drawings are marked as: laser operation console 1, infrared laser beam 2, container 3, power supply of magnetic field generating device 4, power cord of magnetic field generating device 5, laser galvanometer lifting structure 6, laser galvanometer 7, hard alloy sample to be processed 8, sample table 9, magnetic field generator 10. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.

[0030] Obviously, the drawings described below are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios based on these drawings without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in this field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.

[0031] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those of ordinary skill in the art that the embodiments described in this application may be combined with other embodiments without conflict.

[0032] Unless otherwise defined, the technical terms or scientific terms involved in this application should be understood by people with ordinary skills in the technical field to which this application belongs. The words "one", "a", "a", "the" and the like involved in this application do not indicate a quantitative limitation, and may represent the singular or plural. The terms "include", "comprise", "have" and any of their variations involved in this application are intended to cover non-exclusive inclusions; for example, a process, method, system, product or device that includes a series of steps or units (units) is not limited to the listed steps or units, but may also include steps or units that are not listed, or may also include other steps or units inherent to these processes, methods, products or devices. The words "connect", "connected", "coupled" and the like involved in this application are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. The "multiple" / "several" involved in this application refers to two or more. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, "A and / or B" can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the objects before and after are in an "or" relationship. The terms "first", "second", "third", etc. involved in this application are only used to distinguish similar objects and do not represent a specific ordering of the objects.

[0033] The magnetic field assisted surface laser shock strengthening device of the present invention has a structure as follows: Figure 2As shown, it includes a laser operation console 1, an infrared laser beam 2, a container 3, a power supply 4 for a magnetic field generating device, a power cord 5 for a magnetic field generating device, a laser galvanometer lifting structure 6, a laser galvanometer 7, a hard alloy sample 8 to be processed, a sample stage 9, a magnetic field generator 10 and other structures. The laser operation console 1 is used to operate the movement of the laser galvanometer 7 and the working state of the laser galvanometer 7. The hard alloy sample 8 to be processed is placed in the container 3, and deionized water is placed in the container 3. The deionized water covers the hard alloy sample 8 to be processed, and the covering height is 0.2-1.5mm. The magnetic field generator 10 includes two Helmholtz coils, and a uniform magnetic field is formed between the two Helmholtz coils. The sample stage 9 is placed between the two Helmholtz coils, and the container 3 is placed on the sample stage 9. The laser galvanometer lifting structure 6 can drive the laser galvanometer 7 to move, so that the infrared laser beam 2 emitted by the laser galvanometer 7 can correctly impact the target area of ​​the hard alloy sample 8 to be processed. The magnetic field generating device power supply 4 is connected to the magnetic field generator 10 via the magnetic field generating device power supply line 5. The magnetic field generating device power supply 4 is used to provide power to the magnetic field generator 10 and change the magnetic field strength of the magnetic field generator 10 by adjusting the input current.

[0034] The magnetic field assisted surface laser shock strengthening method for cemented carbide of the present invention is further described below in conjunction with specific embodiments:

[0035] The cemented carbide samples used in the examples are commercially available YG8 cemented carbide and YG20 cemented carbide, with YG8 having a bending strength of 1500 MPa and a hardness of 15 GPa. YG20 has a bending strength of 2500 MPa and a hardness of 9 GPa. YG8 cemented carbide is generally used as a tool material for cutting metals, while YG20 cemented carbide is used for forging dies and cold forging dies.

[0036] Embodiment 1,

[0037] In this embodiment, YG8 cemented carbide is used, the magnetic field strength is set to 30 mT, the water confinement layer is 0.8 mm away from the cemented carbide surface, the laser scanning path spacing is 0.1 mm, the laser scanning frequency is 20 KHz, the laser power is 8 W, and the scanning times are 2 times.

[0038] The preparation steps are as follows:

[0039] 1. Use electric spark wire cutting to cut the YG8 cemented carbide sample into block blanks of 30mm*30mm*5mm;

[0040] 2. The YG8 cemented carbide sample was roughly ground using a surface grinder to remove 45 μm of the ablated surface produced by wire EDM, and diamond grinding paste was used to remove the surface wear marks to obtain a flat surface;

[0041] 3. Place the YG8 cemented carbide sample in a beaker containing alcohol and remove impurities such as surface oil by ultrasonic cleaning for 15 minutes to obtain the original cemented carbide sample;

[0042] 4. Place the YG8 cemented carbide sample in a beaker and cover the cemented carbide sample with deionized water as a constraining layer. The water surface of the constraining layer is 0.8 mm higher than the cemented carbide surface.

[0043] 5. Turn on the magnetic field generator and adjust the current and voltage. The magnetic field strength is 30mT. The surface of the YG8 cemented carbide sample is laser-shock-hardened. The laser scanning path spacing range is 0.1mm.

[0044] 6. The surface of the YG8 cemented carbide sample was treated with a pulsed laser shock peening treatment at a wavelength of 1064nm, with a laser scanning path spacing of 0.1mm, a laser scanning frequency of 20KHz, a laser power of 8W, and a scanning number of 2 times, to obtain a cemented carbide with improved mechanical properties.

[0045] The obtained cemented carbide material blank with improved mechanical properties was ground and polished to prepare a 3mm×4mm×30mm specimen, and its mechanical properties were measured as follows: hardness 18.11GPa, relative density 98.1%, and flexural strength 1725.43MPa. Figure 1 The grain size of the sample before and after magnetic field-assisted laser shock strengthening is shown. Figure 1 (a) Original sample, the average grain size is 2.62 μm. Figure 1 (b) The grain size of the sample after magnetic field-assisted laser shock strengthening is 1.06 μm.

[0046] Embodiment 2,

[0047] In this embodiment, YG20 cemented carbide is used, the magnetic field strength is set to 30 mT, the water confinement layer is 0.8 mm away from the cemented carbide surface, the laser scanning path spacing is 0.1 mm, the laser scanning frequency is 20 KHz, the laser power is 8 W, and the scanning times are 2 times.

[0048] The preparation steps are as follows:

[0049] 1. Use electric spark wire cutting to cut the YG20 cemented carbide sample into block blanks of 30mm*30mm*5mm;

[0050] 2. The YG20 cemented carbide sample was roughly ground using a surface grinder to remove 45 μm of the ablated surface produced by wire EDM, and diamond grinding paste was used to remove the surface wear marks to obtain a flat surface;

[0051] 3. Place the YG20 cemented carbide sample in a beaker containing alcohol and remove impurities such as surface oil by ultrasonic cleaning for 15 minutes to obtain the original cemented carbide sample;

[0052] 4. Place the YG20 cemented carbide sample in a beaker and cover the cemented carbide sample with deionized water as a constraining layer. The water surface of the constraining layer is 0.8 mm higher than the cemented carbide surface.

[0053] 5. Turn on the magnetic field generator and adjust the current and voltage. The magnetic field strength is 30mT. The surface of the YG8 cemented carbide sample is laser-shock-hardened. The laser scanning path spacing range is 0.1mm.

[0054] 6. The surface of the YG20 cemented carbide sample was treated with a pulsed laser shock peening treatment at a wavelength of 1064nm, with a laser scanning path spacing of 0.1mm, a laser scanning frequency of 20KHz, a laser power of 10W, and a scanning number of 2 times, to obtain a cemented carbide with improved mechanical properties.

[0055] The obtained cemented carbide material blank with improved mechanical properties was ground and polished to prepare a 3mm×4mm×30mm specimen, and its mechanical properties were measured as follows: hardness 13.92GPa, relative density 97.6%, and flexural strength 2876.4MPa.

[0056] Comparative Example 1:

[0057] In this comparative example, YG8 cemented carbide was used, and the cemented carbide surface was impacted by laser without magnetic field and water protection, which included a laser scanning path spacing of 0.1 mm, a laser scanning frequency of 20 KHz, a laser power of 8 W, and 2 scanning times.

[0058] The preparation steps are as follows:

[0059] 1. Use electric spark wire cutting to cut the YG8 cemented carbide sample into block blanks of 30mm*30mm*5mm;

[0060] 2. The YG8 cemented carbide sample was roughly ground using a surface grinder to remove 45 μm of the ablated surface produced by wire EDM, and diamond grinding paste was used to remove the surface wear marks to obtain a flat surface;

[0061] 3. Place the YG8 cemented carbide sample in a beaker containing alcohol and remove impurities such as surface oil by ultrasonic cleaning for 15 minutes to obtain the original cemented carbide sample;

[0062] 4. Laser shock peening treatment was performed on the surface of YG8 cemented carbide sample, and the laser scanning path spacing range was 0.1mm

[0063] 5. The surface of the YG8 cemented carbide sample was treated with a 1064nm pulsed laser shock peening process. The laser scanning path spacing was 0.1mm, the laser scanning frequency was 20KHz, the laser power was 8W, and the scanning times were 2 times. The cemented carbide with improved mechanical properties was obtained.

[0064] The obtained cemented carbide material blank with improved mechanical properties was ground and polished to prepare a 3mm×4mm×30mm specimen, and its mechanical properties were measured as follows: hardness 14.15GPa, relative density 94.4%, and flexural strength 1370.1MPa.

[0065] The research results show that the alternating magnetic field assisted laser shock strengthening treatment significantly improves the bending strength, hardness and relative density of cemented carbide, and reduces the average grain size to 1.06μm. The surface oxide layer is removed during the laser shock process, and high residual compressive stress is generated under the high-pressure shock wave. The internal metal phase migrates to the surface and fills between the WC particles to improve the grain boundary strength. The present invention removes the surface oxide layer and refines the grains through the alternating magnetic field assisted laser shock strengthening to produce a gradient structure on the surface layer, effectively improving the mechanical properties of cemented carbide.

[0066] It can be understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solution described in the implementation of the calculation method of the present invention. Ordinary technicians in the field should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effect; as long as the requirements of the calculation method are met, they are all within the protection scope of the present invention.

Claims

1. A magnetic field assisted surface laser shock strengthening device for cemented carbide, characterized by: The invention comprises a laser galvanometer (7), a container (3) and a magnetic field generator (10). A hard alloy sample (8) to be processed is placed in the container (3). The hard alloy sample (8) to be processed is covered with deionized water in the container (3). The magnetic field generator (10) comprises two Helmholtz coils. A uniform magnetic field is formed between the two Helmholtz coils. The container (3) is placed between the two Helmholtz coils. The laser galvanometer (7) is aligned with the hard alloy sample (8) to be processed. The laser galvanometer (7) can generate an infrared laser beam (2) to perform laser shock strengthening on the hard alloy sample (8) to be processed.

2. The magnetic field assisted surface laser shock hardening device of cemented carbide according to claim 1, characterized in that: The magnetic field generator (10) is connected to a magnetic field generating device power supply (4) via a magnetic field generating device power supply line (5), and the magnetic field generating device power supply (4) can change the magnetic field intensity of the magnetic field generator (10) by changing the input current.

3. The magnetic field assisted surface laser shock hardening device of cemented carbide according to claim 1, characterized in that: It also includes a laser operation console (1), a laser galvanometer lifting structure (6) and a sample stage (9), wherein the laser operation console (1) includes a control device and a display screen, the laser galvanometer lifting structure (6) includes a lifting motor and a lifting rod, the laser galvanometer (7) is mounted on the lifting rod, and the lifting rod is mounted on the lifting motor, the control device is connected to the lifting motor signal, the control device can control the lifting motor to operate so as to lift the lifting rod, the control device is connected to the display screen, and the display screen is used to display the control information of the control device, the sample stage (9) is located between the two Helmholtz coils, and the container (3) is placed on the sample stage (9).

4. A method for magnetic field-assisted surface laser shock strengthening of cemented carbide, characterized in that: The magnetic field assisted surface laser shock strengthening device for cemented carbide as claimed in claim 1 specifically comprises the following steps: S1, cutting the cemented carbide into block blanks by electric spark wire cutting; S2. Roughly grind the block blank to remove the ablated surface produced by wire EDM to obtain a smooth surface; S3, cleaning the block blank to remove oil and impurities on the surface, and obtaining a hard alloy sample to be processed (8); S4, placing the hard alloy sample (8) to be processed into the container (3), and covering the hard alloy sample (8) to be processed with deionized water as a constraining layer; S5, placing the container (3) between the two Helmholtz coils, setting the input current, input voltage and frequency of the magnetic field generator (10) so that each Helmholtz coil generates an alternating magnetic field, and the magnetic field between the two Helmholtz coils is a uniform magnetic field; S6, starting the laser galvanometer (7), the laser galvanometer (7) performs laser shock peening treatment on the surface of the hard alloy sample (8) to be processed through the infrared laser beam (2), and obtains the hard alloy induced by laser shock peening.

5. A magnetic field-assisted surface laser shock strengthening method for cemented carbide according to claim 4, characterized in that: in S2, the block blank is roughly ground using a surface grinder to remove the ablated surface generated during electric spark wire cutting, the ablated surface removal depth range is 10-50μm, and the surface wear marks are removed using diamond grinding paste to obtain a flat surface, and the surface roughness of the flat surface is Ra0.1-0.

2.

6. A magnetic field-assisted surface laser shock strengthening method for cemented carbide according to claim 4, characterized in that: in S3, the block blank is placed in a container filled with alcohol, and the surface oil and impurities are removed by ultrasonic cleaning for 15 minutes to obtain a cemented carbide sample (8) to be processed.

7. The method for surface laser shock strengthening of cemented carbide by magnetic field assistance according to claim 4, characterized in that: In S4, the ionized water serves as a constraining layer to cover the hard alloy sample (8) to be processed, and the water surface of the constraining layer is 0.2-1.5 mm higher than the upper surface of the hard alloy sample (8) to be processed.

8. The method for magnetic field-assisted surface laser shock hardening of cemented carbide according to claim 4, characterized in that: In S5, the input current of the magnetic field generator (10) is 10-15A, the input voltage is 150-250V, the frequency is 40-50Hz, and the uniform magnetic field intensity generated by the two Helmholtz coils is within 0-60mT.

9. A magnetic field-assisted surface laser shock strengthening method for cemented carbide according to claim 4, characterized in that: in S6, the power of the infrared laser beam (2) generated by the laser galvanometer (7) is 2-16W, the laser scanning path spacing range is 0.05mm-0.15mm, the laser spot overlap rate is 50%, and the number of scans of the laser shock strengthening cemented carbide sample (8) to be processed is in the range of 1 to 5 times.

10. The method for surface laser shock strengthening of cemented carbide by magnetic field assistance according to claim 4, characterized in that: The wavelength of the infrared laser beam (2) is 1064 nm.

Citation Information

Patent Citations

  • Method and device for strengthening ferromagnetic metal shocked by static magnetic field coupled laser

    CN118186202A